A Linguistic Study Of Adverbials As Ellipsis In English And Vietnamese - Đoàn Thị Kim Nguyệt (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Adverbials can be considered as an attractive and popular phenomenon of every language by linguists. In reality, a lot of researches have been done on adverbials. Nevertheless, there has been so far no study relating to adverbials as ellipsis. Hence, this thesis is to study syntactic features and cohesive devices of English and Vietnamese adverbials as ellipsis. The analysis made use of 160 adverbials as ellipsis in English and 160 ones in Vietnamese taken from the written novels, stories and on the Internet. The study is carried out based on the theories of linguistic analysis and a combination of a variety of methods, namely qualitative and quantitative methods, descriptive and contrastive ones. The study focuses on analyzing English and Vietnamese adverbials as ellipsis in order to find out similarities and differences of these adverbials as ellipsis in terms of syntactic features and cohesive devices. In terms of syntactic features, English adverbials as ellipsis have adjuncts, disjuncts and conjuncts. However, Vietnamese adverbials as ellipsis only have adjuncts and conjuncts. In terms of cohesive devices, English and Vietnamese adverbials as ellipsis can be divided into two main types such as grammatical cohesion consisting of reference, substitution, ellipsis, conjunction and lexical cohesion including reiteration and collocation. Based on the findings, the thesis provides some implications for teaching and learning adverbials as ellipsis as well as some suggestions for further studies relating to adverbials as ellipsis.